Traditional Tibetan medicine to fight against COVID-19: Basic theory and therapeutic drugs - Zhang, Kun; Wang, Lijie; Peng, Jiayan; Sangji, Kangzhuo; Luo, Yuting; Zeng, Yujiao; Zeweng, Yongzhong; Fan, Gang (Frontiers in Pharmacology, 2023)
The Coronavirus Diseases 2019 (COVID-19) has been rapidly spreading globally and has caused severe harm to the health of people and a substantial social burden. In response to this situation, experts around the world have considered various treatments, including the use of traditional medicine. Traditional Tibetan medicine (TTM), one of the traditional medicines in China, has played an important role in the treatment of infectious diseases in history. It has formed a solid theoretical foundation and accumulated rich experience in the treatment of infectious diseases. In this review, we provide a comprehensive introduction to the basic theory, treatment strategies, and commonly used drugs of TTM for the treatment of COVID-19. In addition, the efficacies and potential mechanisms of these TTM drugs against COVID-19 are discussed based on available experimental data. This review may provide important information for the basic research, clinical application and drug development of traditional medicines for the treatment of COVID-19 or other infectious diseases. More pharmacological studies are needed to reveal the therapeutic mechanisms and active ingredients of TTM drugs in the treatment of COVID-19.